The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jcph.1424
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Pharmacodynamics of the Autotaxin Inhibitor GLPG1690 in Healthy Subjects: Phase 1 Randomized Trials

Abstract: GLPG1690 is a novel autotaxin inhibitor in development for the treatment of idiopathic pulmonary fibrosis (IPF). We report phase 1 studies investigating the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of GLPG1690 in healthy subjects. We performed a first‐in‐human randomized, double‐blind, placebo‐controlled trial of single (20, 60, 150, 300, 600, 1000, 1500 mg) and multiple (14 days: 150 mg twice daily; 600 and 1000 mg once daily) ascending oral doses of GLPG1690 (NCT02179502), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 19 publications
(53 reference statements)
4
20
1
Order By: Relevance
“…GLPG1690 showed superior results compared to pirfenidone and was similar to nintedanib, a tyrosine kinase inhibitor, in reducing the Ashcroft fibrotic score and collagen levels. 247 GLPG1690 was already tested in humans in order to test the safety, pharmacokinetics and pharmacodynamics of its doses, 248 and was well tolerated in a Phase 2a study (FLORA study) involving 23 patients with IPF. Treated patients had reduced plasma LPA C18:2 levels and showed improvement of disease control, such as stabilized FVC after 12 weeks of treatment.…”
Section: Lpa Signaling As a Therapeutic Targetmentioning
confidence: 99%
“…GLPG1690 showed superior results compared to pirfenidone and was similar to nintedanib, a tyrosine kinase inhibitor, in reducing the Ashcroft fibrotic score and collagen levels. 247 GLPG1690 was already tested in humans in order to test the safety, pharmacokinetics and pharmacodynamics of its doses, 248 and was well tolerated in a Phase 2a study (FLORA study) involving 23 patients with IPF. Treated patients had reduced plasma LPA C18:2 levels and showed improvement of disease control, such as stabilized FVC after 12 weeks of treatment.…”
Section: Lpa Signaling As a Therapeutic Targetmentioning
confidence: 99%
“…Moreover, potent (IC50 2 nM), long term (3 weeks) pharmacological inhibition of ATX with PF-8380 (120 mg/Kg - 4 times the effective concentration; PO; bid) had no effects in survival or gross pathology of major organs ( 135 ), suggesting that ATX pharmaceutical targeting is safe and well tolerated in mice. In humans, GLPG1690 was reported to be well tolerated in a phase 1 randomized clinical trial (NCT02179502), safe and efficacious in a phase 2a randomized placebo-controlled clinical trial (NCT02738801), supporting ATX inhibition as a novel treatment for IPF ( 136 , 137 ). In addition, administration of BBT-877, another orally available small molecule inhibitor targeting ATX (IC50 ~6.7 nM), to healthy volunteers in a phase I clinical trial (NCT03830125), did not reveal severe adverse events ( 138 , 139 ).…”
Section: Pharmacologic Targeting Of Atx As An Additional Therapeutic Option In Covid-19mentioning
confidence: 99%
“…The pharmacokinetics (PK) of ziritaxestat have been reported separately. 18 Ziritaxestat is rapidly absorbed and eliminated, with exposure to parent increasing in a dose‐proportional manner. In vitro human recombinant cytochrome P450 (CYP) studies indicated that ziritaxestat was primarily metabolized by CYP3A4 with minor contributions (maximum of 2.1%) to metabolism from other phase 1 enzymes.…”
mentioning
confidence: 99%